1990
DOI: 10.1177/002221949002300110
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Testing of a Cognitive Model to Account for Neuropsychological Functioning Underlying Arithmetic Problem Solving

Abstract: The efficacy of a cognitive-based arithmetic problem-solving model (Dinnel, Glover, & Halpain, in press; Dinnel, Glover, & Ronning, 1984) was tested using 989 students with learning disabilities. Comprehensive neuropsychological test battery information was used to predict composite arithmetic test performance as a means of examining the utility of this model. Results of this study offer support for Dinnel et al.'s (Dinnel, Glover, & Halpain, in press; Dinnel, Glover, & Ronning, 1984) model in accounting for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Since JLO but not Gv predicts math skill, it would seem that spatial perception is more important to math achievement than general visual processing. This interpretation is consistent with past studies that have shown such spatial tasks as Pattern Analysis from the Stanford-Binet IV and WISC-R Block Design to be related to math skills (Assel et al, 2003;Batchelor, Gray, & Dean, 1990).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Since JLO but not Gv predicts math skill, it would seem that spatial perception is more important to math achievement than general visual processing. This interpretation is consistent with past studies that have shown such spatial tasks as Pattern Analysis from the Stanford-Binet IV and WISC-R Block Design to be related to math skills (Assel et al, 2003;Batchelor, Gray, & Dean, 1990).…”
Section: Discussionsupporting
confidence: 92%
“…However, the WJ-R visual factor (Gv) emphasizes aspects of visual perceptual processing (e.g., closure speed, visual memory) to a greater extent than spatial ability, making the Gv factor perhaps less sensitive to the type of visual abilities (i.e., spatial visualization and spatial relations) important in math skill development (Geary, Hamson, & Hoard, 2000;McGrew, Flanagan, Keith, & Vanderwood, 1997). In support of this interpretation, others using purer measures of visuospatial ability (e.g., WAIS Block Design: Batchelor, Gray, & Dean, 1990; Standford-Binet IV Pattern Analysis and Copying: Assel et al, 2003;Benton Judgment of Line Orientation: Riccio & Hynd, 1992) have found a relationship between visuospatial ability and math skill.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…(x) Not all reading disabled children will necessarily have serious arithmetic disability (Guttman, 1937;Goodstein and Kahn, 1974). (xi) Arithmetic disorders frequently co-occur with reading and spelling disorders (Fletcher and Loveland, 1986;Batchelor et al, 1990;Miles and Miles, 1992). (xii) Subtle cognitive deficits in symbolic or representational thinking, temporal-sequential organization, verbal memory, and rate of verbal processing may underlie language deficits in children.…”
Section: The Concept and Nature Of Dyscalculiamentioning
confidence: 99%